MUTUAL VALIDATION OF THREE PROGRAMS FOR NUMERIC ANTENNA COMPUTATIONS - Efanov, Andrew A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The numerical results obtained by three different codes, GALNEC, WARAN and NEC-2 are compared for thin dipoles and thick ones with hemispherical end caps and for arrays of such collinear dipoles. The electric field integral equation and Galerkin’s method are used in the code GALNEC where solid thick dipole bodies are implemented. Mei’s (1965) integral equation and collocation technique are wed in the code WARAN, where thick dipoles are simulated as arrays of thin wires. Good agreement has been obtained for current distri- butions and input and mutual impedances. [Vol. 10, No. 2 (1995), pp 96-101]